Unveiling RNA structure-mediated regulations of RNA stability in wheat - Haidan Wu; Haopeng Yu; Yueying Zhang; Bibo Yang; Wenqing Sun; Lanying Ren; Yuchen Li; Qianqian Li; Bao Liu; Yiliang Ding; Huakun Zhang (Nature Communications)
Abstract Despite the critical role of mRNA stability in post-transcriptional gene regulation, research on this topic in wheat, a vital agricultural crop, remains unclear. Our study investigated the mRNA decay landscape of durum wheat (Triticum turgidum L. ssp. durum, BBAA), revealing subgenomic asymmetry in mRNA stability and its impact on steady-state mRNA abundance. Our findings indicate that the 3’ UTR structure and homoeolog preference for RNA structural motifs can influence mRNA stability, leading to subgenomic RNA decay imbalance. Furthermore, single-nucleotide variations (SNVs) selected for RNA structural motifs during domestication can cause variations in subgenomic mRNA stability and subsequent changes in steady-state expression levels. Our research on the transcriptome stability of polyploid wheat highlights the regulatory role of non-coding region structures in mRNA stability, and how domestication shaped RNA structure, altering subgenomic mRNA stability. These results illustrate the importance of RNA structure-mediated post-transcriptional gene regulation in wheat and pave the way for its potential use in crop improvement.